Female Directors, Mechanisms for Corporate Governance and Agency Cost - Alluwia, Farissha; Sarun, Anuar (International Business Education Journal, 2018)
This paper aims to investigate the effect of the presence of female board directors and corporate governance mechanisms on agency cost focusing on board of directors’ and audit committee’s characteristics. The samples used in this study consisted of 150 companies listed on Bursa Malaysia in trade and services sector from 2010 until 2013. The dependent variable in this research is agency cost. Based on the extensive literature review, this study applied two agency cost proxies, which are asset utilisation ratio (AUR) and expense ratio (ER). Meanwhile, there are seven independent variable which are female board directors, board size, CEO duality, independent directors, size of the audit committee, audit committee meeting and audit quality. Data was analysed using descriptive statistics, correlation analysis and linear regression. The empirical result reveals that female board directors, board size, CEO duality, independent directors, and audit quality have a significantly negative relationship with agency cost using asset utilisation ratio (AUR) as the proxy. Meanwhile, for expense ratio (ER) proxy, the result shows that female board directors, the size of the audit committee, and audit quality have a significantly negative relationship with agency cost. Besides that, with these research findings, the corporate companies could have a better and thorough understanding about corporate governance which would help them decrease their agency cost from time to time. The findings also could be used as the reference and guidance in establishing company policies or finance policies in decreasing the company’s agency cost. Plus, these findings enrich the literature in corporate companies, thus help future researchers. Finally, the researcher presented some suggestions and recommendations for future studies to diversify the sectors of the selected companies so that the data obtained will be wider and larger. Besides, future researchers may extend the data period from four years up to 10 years.